2020
DOI: 10.1002/hpja.436
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of COVID‐19 on children’s physical activity levels in NSW, Australia

Abstract: LETTER TO THE EDITOR physical activity and screen time observed could persist and threaten a further deterioration in global inactivity rates. Programmatic and policy strategies such as Active Kids could arguably be reoriented towards promoting physical activity and reduced screen time during pandemic periods as well as in usual times to good effect. Such efforts should focus on young people who are insufficiently active, those from lower socioeconomic areas, and those from culturally and linguistically divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 9 publications
0
25
4
3
Order By: Relevance
“…Several studies reported on a considerable disengagement in physical activity during the lockdown. 36 , 37 , 38 , 39 , 40 While this appears true for most of our respondents, it is noteworthy that changes for the better were reported by more than one-third of girls and boys. In a study of lifestyle behaviours in Irish adolescents (12–18 years old) during the first lockdown, 41 20% and 30% of students reported exercising more and about the same, respectively, than 50% exercising less than pre-pandemic.…”
Section: Discussionmentioning
confidence: 53%
“…Several studies reported on a considerable disengagement in physical activity during the lockdown. 36 , 37 , 38 , 39 , 40 While this appears true for most of our respondents, it is noteworthy that changes for the better were reported by more than one-third of girls and boys. In a study of lifestyle behaviours in Irish adolescents (12–18 years old) during the first lockdown, 41 20% and 30% of students reported exercising more and about the same, respectively, than 50% exercising less than pre-pandemic.…”
Section: Discussionmentioning
confidence: 53%
“…Results consistently showed reported decreases in PA time in children and youth, and this was demonstrated repeatedly in both longitudinal 66 , 67 , 68 , 69 , 70 , 72 , 73 , 74 , 75 , 77 and cross-sectional designs. 78 , 80 , 84 , 92 , 102 , 103 , 107 , 109 , 114 , 117 , 118 This result was echoed by those of other studies using similar constructs, including exercise time, 100 , 104 , 115 energy expenditure, 79 and MVPA. 116 , 121 , 122 , 123 However, 3 longitudinal research studies reported decreases in sports-related PA 65 , 73 , 77 but not in school and leisure-time PA, 73 habitual activity, 65 and nonorganized sports-related PA. 65 It is worth noting that although studies consistently identified overall decreases in PA, there were groups of children and youth in some studies who reported stability 125 or an increase 65 , 132 in unstructured PA. Several studies reported changes in the proportion of children and youth meeting PA guidelines.…”
Section: Resultsmentioning
confidence: 85%
“… 99 The remaining studies relied on nonvalidated measures of PA through self-reported questionnaires constructed by the researchers. These questionnaires quantified PA behaviors using several approaches, including subjective reporting of changes, 72 , 78 , 100 , 101 , 102 , 103 , 104 daily duration of PA, 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 days per week with at least 60 min of MVPA, 71 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 or frequency of weekly PA, 125 weekly PA duration, 76 , 77 , 118 , 126 outdoor activity, 78 , 116 , 119 , 127 ±3 h of PA per week, 128 , 129 percentage of time spent in PA, 130 , 131 or other means, as detailed in the list of included studies in Supplementary File 5. We identified 3 secondary data analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Despite the existing literature, further research is needed for a more comprehensive understanding of the effects of the COVID-19 pandemic on children's and adolescents' lifestyle, and on the relationship between lifestyle behaviours and well-being. Very few studies extended their assessment beyond June 2020, [12][13][14] and only one small (n=19) longitudinal study assessed lifestyle changes up to 2021. 15 In addition, studies assessing the associations between lifestyle and wellbeing during the pandemic were all based on a single-behaviour approach.…”
Section: Introductionmentioning
confidence: 99%